2020
DOI: 10.1371/journal.pone.0244438
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of intoxication events and patient outcomes in Taiwan: A nationwide population-based observational study

Abstract: Background Intoxicated patients were frequently managed in the emergency departments (ED) with few studies at national level. The study aimed to reveal the incidence, outcomes of intoxications and trend in Taiwan. Methods Adults admitted to an ED due to an intoxication event between 2006 and 2013 were identified using the Taiwan National Health Insurance Research Database. The rate of intoxication and severe intoxication events, mortality rate, hospital length of stay (LOS), and daily medical costs of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…According to the World Health Organization mortality database, over 700,000 people die by committing suicide each year, which makes it the fourth leading cause of death among people under the age of 30 years [3]. A nationwide population study in East Asia revealed that suicide attempts in patients with psychiatric illness occurred more frequently and exhibited a more serious pattern [4]. European data indicated significant gender differences in suicide methods and lethality, with men often choosing more violent and intentional methods [5].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization mortality database, over 700,000 people die by committing suicide each year, which makes it the fourth leading cause of death among people under the age of 30 years [3]. A nationwide population study in East Asia revealed that suicide attempts in patients with psychiatric illness occurred more frequently and exhibited a more serious pattern [4]. European data indicated significant gender differences in suicide methods and lethality, with men often choosing more violent and intentional methods [5].…”
Section: Introductionmentioning
confidence: 99%